Disruptive Technologies and Open Science: How Open Should Open Science Be? A ‘Third Bioethics’ Ethical Framework. - Spitale, Giovanni; Germani, Federico; Biller-Andorno, Nikola (Science & Engineering Ethics, 2024)
This paper investigates the ethical implications of applying open science (OS) practices on disruptive technologies, such as generative AIs. Disruptive technologies, characterized by their scalability and paradigm-shifting nature, have the potential to generate significant global impact, and carry a risk of dual use. The tension arises between the moral duty of OS to promote societal benefit by democratizing knowledge and the risks associated with open dissemination of disruptive technologies. Van Rennselaer Potter's ‘third bioethics’ serves as the founding horizon for an ethical framework to govern these tensions. Through theoretical analysis and concrete examples, this paper explores how OS can contribute to a better future or pose threats. Finally, we provide an ethical framework for the intersection between OS and disruptive technologies that tries to go beyond the simple ‘as open as possible’ tenet, considering openness as an instrumental value for the pursuit of other ethical values rather than as a principle with prima facie moral significance.